Functional Implementation of Multiple Traversals Program with Attribute Grammars in Scala - Kouamou, Georges Edouard; Nenkam, Thierry; Fotsing, Bernard Talla (Transactions on Engineering and Computing Sciences, 2017)
Attribute grammars are a powerful specification paradigm for many language processing tasks, particularly the semantic analysis of programming languages. To functionally evaluate attributes grammar in Scala, the studies to date combine Scala with Kiama. Another study relies on object algebra, is implemented in Scala but with multiple evaluation of attributes. The purpose of this study is to use only the Scala language, in order to provide a solution to the multiple traversals of derivation trees. This approach extends the object algebra with the visit-sequences which let us increase the number of folding, thus avoid the multiple evaluation of some attributes, and the result obtained from this experience gives way to the functional modeling of interactive systems. The illustration is made on the Repmin problem.